Imaging of benign and malignant cystic pancreatic lesions and a strategy for follow up - Bhosale, Priya (Baishideng Publishing Group Co., Limited, 2010)
Cystic lesions in a variety of organs are being increasingly recognized as an incidental finding on cross-sectional imaging. These lesions can be benign, premalignant or malignant. When these cystic lesions are small it can be difficult to characterize them radiologically. However, with appropriate clinical history and knowledge of typical imaging features of cystic pancreatic lesions this can enable accurate diagnosis and thus guide appropriate treatment. In this review, we provide an overview of the most common types of cystic lesions and their appearance on computer tomography, magnetic resonance imaging and ultrasound. We will also discuss the follow up and management strategies of these cystic lesions.